Role of Education and Awareness in Empowering Hill Women of Uttarakhand about Functioning of Panchayati Raj Institutions - Maikhuri, Rama (JOURNAL OF INDIAN EDUCATION, 2010)
At present, all over the country, states have delegated powers to Panchayati Raj Institutions (PRIs) in terms of article 243 and the Eleventh Schedule of the Constitution have decentralized governance up to the village level. The active involvement and participation of PRIs and its mandated functions in most of the sectors of rural economy is urgently required which would not only provide livelihood and food security locally but also contribute towards minimising existing pressure on natural resources. The hill women play a significant role in natural resource management, on which the rural livelihood and the very survival of hill families/communities depend. Despite of that, women have been and still are excluded from production of and representation in many socio-cultural and political decision making activities. Therefore, there is need to provide detailed information about rural development programmes/activities (being executed by the state/central governments and their line departments) and make them empower about roles and functions of PRIs through education and awareness. The present paper describes in detail that how hill women are actively involved in various mandated activities of PRIs for hill area development.